Media Berhitung Berbasis Java dalam Pembelajaran Matematika - Siti Waryuningsih (JKPM (Jurnal Kajian Pendidikan Matematika), 2016)
The aims of this research was to develop java-based arithmatics media in learning mathematics. The experiment was conducted on students of SD Negeri Gedong 06 Pagi Jakarta at the fifth grade. The research model used to develop Java-based arithmetic media are ADDIE instructional model. Research products tested to one media expert, three mathematics subject matter experts, one expert instructional design, and three students at the trial of one to one. From the test results obtained an overall average has a formative evaluation criteria, including the overall average of the evaluation of one to one to count java-based arithmatics media program in mathematics for class V SD is good. Based on the findings, it was concluded that the media count based on Java in mathematics for class V SD were developed in accordance with the model of instructional development. Suggestions regarding the media to be more attention on the development of the visualization of the concept of matter, order and presentation format, the need for technical skills in the making, the adjustment of the layout, the sound effects are also shown and color match more interesting.